Organoleptic, Chemical and Physical Characteristics of Cookies Substituted with Bamboo Shell Meat Flour (Solen sp.) - Trisyani, Ninis; Syahlan, Qonitah (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
Bamboo shells are a class of bivalves that have economic value and high nutritional content, so it is necessary to diversify products in the form of cookies that have high protein and mineral content and increase consumption of fishery products in Indonesia. This study aims to determine the effect of the combination of doses of bamboo shell meat flour and different flavors on the organoleptic value of cookies, proximate content and physical properties of the selected cookies. The design used was factorial RAL, namely treatment with substitution doses of bamboo shell meat flour (Solen sp.) as much as 0%, 10%, and 20% and different flavor treatments, namely seaweed and pizza, with 3 replications. The average organoleptic value of the selected hedonic cookies is the cookies substituted with 10% bamboo mussel meat flour with seaweed flavor with the organoleptic values of appearance, texture, taste and aroma respectively 4.06; 4.39; 4.67; and 4.43 on a scale of 1-5. The results of the proximate test showed that cookies with a substitution of 10% bamboo shell meat flour with seaweed flavor met the requirements of SNI 012973-1992 for cookies: water content 4.02%, ash content 0.11%, protein 10.07%, fat 12.34%, carbohydrates 73.46%, energy 500.65 kkla/100 g, color L=49.26 a=+9.4 b=21.34, hardness 2413.98 gf/cm and Aw 0.51%.. Consumption of 3 pieces of cookies can meet the needs of 20% protein Nutritional Sufficiency Rate in the 7-9 year age group.